Bank market concentration and efficiency in the European Union: a panel Granger causality approach - Ferreira, Cândida (2012)
The relationships between bank market concentration and bank efficiency are of particular relevance in the European Union (EU), but they remain controversial. Using a panel Granger causality approach, this paper contributes to the literature, testing not only the causality running from bank market concentration to bank efficiency, but also the reverse causality running from efficiency to concentration. The results obtained confirm the relative complexity of these causality relationships, although they generally point to a negative causation running both from concentration to efficiency and from efficiency to concentration. These findings are in line with the Structure Conduct Performance (SCP) paradigm and the suggestions that the increase of the banks’ market power will contribute to inefficiency, since these banks will face less competition to obtain more output results with less input costs. Our results suggest that within this panel of all 27 EU countries over a relatively long time period, from 1996 to the onset of the 2008 financial crisis, the more cost-efficient commercial and savings banks operated in less concentrated markets.